Human Embryo Transfer - Allahbadia, Gautam N.; Chillik, Claudio F. (Springer India : Imprint: Springer, 2015)
This concise work on embryo transfer is yet another contribution to the persevering effort to disseminate latest information on the science and skill of performing a traumatic and successful embryo transfer. It is the most critical culmination of the assisted reproductive technology (ART) stimulation cycle, and a rate-limiting step in dictating the success of treatment. The well-worded chapters draw the reader's attention to significant aspects before initiating the actual embryo transfer, such as possible causes of failure at the embryo transfer stage, uterine evaluation, mock embryo transfer (ET), experience of the physician, and the use of ultrasound-guidance to monitor ET. The protocol for difficult transfers, variables that affect the success of ET, and the influence of the catheter used for ET have also been dealt with. The unique feature of this book is its pragmatic approach that can translate into solutions to the numerous frustrating ART failures that more often than not, may be attributed to an inefficient ET procedure. It helps the reader understand the integrity of embryo transfer, unravel its obvious simplicity and bridge the success between the several steps of ART. By highlighting the impeding problems associated with ET procedure and providing valid, scientific solutions, this stimulating edition will help the readers improve the ART success rates in their clinical practice. .